Trend Analysis Based Educator Planning - Saifuddin Chalim; Gatot Sujono; Fadly Usman (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Many cases show that the condition of existing resources will cause problems for every educational institution. There are two possibilities; (1) If the number of teachers is lower than the ideal number, and (2) If the number of existing teachers exceeds the ideal number needed. Therefore, each institution must plan teacher needs with a scientific approach, both qualitative and quantitative. This study aims to plan teacher needs for the 2018/2019 school year at the International Standard Madrasah, Amanatul Ummah, Pacet, Mojokerto, East Java. The teacher planning used in this study is a trend analysis predicting the number of new students in 2018/2019 which will then be the basis for determining the number of study groups. Based on the number of study groups, it is then determined by the needs of teachers, especially those who are subject to national testing. The results showed that the composition of the teacher was needed, based on the basic and current needs of the trend analysis.